Analysis of the barriers of mental distress disclosure in medical inpatients in Taiwan. (August 2015) - Han, Der-Yan; Lin, Yi-Yin; Liao, Shih-Cheng; Lee, Ming-Been; Thornicroft, Graham; Wu, Chia-Yi
Background: Disclosure of mental distress to physicians is important for mental illness identification, early referrals and proper treatment to prevent suicide. Little is known about what affects mental health communication in the clinical settings in the Chinese societies. Aims: The study aimed to identify the demographic, psychosocial and medical factors related to people with non-disclosure of their mental distress. Methods: We interviewed a series of consecutive inpatients from two medical wards of a general hospital in northern Taiwan. We collected depressive symptoms (the Patient Health Questionnaire, PHQ-9), living arrangement, threatening life events, suicide risks (i.e. past self-harm history, lifetime suicide ideas and hopelessness) and recent experience of mental distress disclosure. Furthermore, we explored the reasons of non-disclosure. Results: A total of 230 medical inpatients agreed to participate (53.5% males). The results indicated that only 5.7% actually communicated their mental health concerns, and that 12.3% were willing to talk about their mental health problems. Among the 69 (30%) depressed participants (PHQ-9 score ≥ 10 points), the disclosure rate was low (8.7%) and the wish to talk about mental distress was also low (10.3%). After adjustment, living alone (OR = 7.58, 95% CI = 1.56–36.91) and having stressful life events (OR = 3.68, 95% CI = 1.09–12.46) remained significant in predicting disclosure of mental distress. The 109 participants attributed their refusal of communicating mental distress as medical-related attributes, subjective perceptions or sociocultural factors. Conclusion: Communication of mental distress in medical settings was uncommon due to medical or psychosocial barriers in Taiwan. Skill training to facilitate disclosure in medical education and public campaigns to improve knowledge of depression and enhance help-seeking deserve more attention, particularly under the influence of stigma in the Chinese societies.